PENGARUH KEPUASAN KERJA DAN IKLIM ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR PADA KARYAWAN DARAT PT. PELINDO MARINE SERVICE - Novianita Cyntia Darsono; Nurul Sih Widanti; Tri Budi Marwanto (Fakultas Psikologi Universitas Hang Tuah, 2022)
This study aims to determine the effect of job satisfaction and organizational climate on organizational citizenship behavior. This study uses a quantitative approach with survey research methods. This study uses quantitative methods using a questionnaire as a research instrument. The number of subjects is 100 employees of PT Pelindo Marine Service which is determined by probability sampling. There are three research scales, namely the scale of job satisfaction (X1), organizational climate (X2), organizational citizenship behavior (Y). The data analysis technique used multiple linear regression. Previously, the data had to be ensured that it passed the instrument test and prerequisite test. The results of the hypothesis analysis show that together the variables of job satisfaction (X1) and organizational climate (X2) significantly affect organizational citizenship behavior (Y) with a percentage of 79.1%. This research suggest PT Pelindo Marine Service in optimizing employee work and fostering enthusiasm in employees to continue to make positive contributions so that they are even better by getting used to organizational citizenship behavior (OCB).